2022
DOI: 10.1111/mmi.14904
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium falciparum parasitophorous vacuole protein P113 interacts with the parasite protein export machinery and maintains normal vacuole architecture

Abstract: Infection with Plasmodium falciparum parasites results in approximately 627,000 deaths from malaria annually. Key to the parasite’s success is their ability to invade and subsequently grow within human erythrocytes. Parasite proteins involved in parasite invasion and proliferation are therefore intrinsically of great interest, as targeting these proteins could provide novel means of therapeutic intervention. One such protein is P113 which has been reported to be both an invasion protein and an intracellular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Previously, it has been shown that the protein P113 binds to the N-terminus of PfRh5 and postulated that its glycosylphosphatidylinositol anchor bound the RCR complex to the merozoite membrane 27 . However, recent studies have shown that P113 function was not required for P. falciparum growth and is unlikely to be the membrane anchor for the RCR complex 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that the protein P113 binds to the N-terminus of PfRh5 and postulated that its glycosylphosphatidylinositol anchor bound the RCR complex to the merozoite membrane 27 . However, recent studies have shown that P113 function was not required for P. falciparum growth and is unlikely to be the membrane anchor for the RCR complex 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, L1 and L2 adopt the same fold as rhamnose- binding lectins and therefore the same fold as PfP113 29 (Extended Data Fig. 7c), a proposed binding partner of PfRH5 that was previously thought to anchor PfRH5 to the merozoite surface 30 , but which was recently disputed as a surface protein 31 . The large disordered internal loop where PfRIPR is cleaved links L1 and L2.…”
Section: The Structure Of Pfriprmentioning
confidence: 97%
“…Interestingly, even though the 120 aa cargo co-localised with EXP2, it was never observed inside EXP2 loops (Fig 4A, white arrows) which we commonly observe for the exported reporter Hyp1-Nluc-DH upon WR trapping (59,62). These loops are thought to represent accumulated trapped cargo unable to be transported by the PTEX complex at the PVM (59).…”
Section: The Fp2a 120 Aa Reporter Displays Increased Co-localisation ...mentioning
confidence: 77%